2011
DOI: 10.1063/1.3645637
|View full text |Cite
|
Sign up to set email alerts
|

Spin transistor using magnetic tunnel junctions with half-metallic Co2MnSi Heusler alloy electrodes

Abstract: We fabricated a spin transistor structure that consisted of two magnetic tunnel junctions with half-metallic Co2MnSi electrodes. Transient responses were observed by applying pulsing gate voltage. Output currents were controlled by both the source-drain and gate voltage and magnetic configuration of the Co2MnSi. The drain current increased around 3000 times at a source-drain voltage of 0.01 V and anti-parallel magnetic configuration, when a gate voltage of 1 V peak-to-peak was applied. In addition, the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Should the development of fully spin-polarized materials succeed, the field of spintronics would boost the electronic industry with much smaller and robust devices with intrinsic memory. Improvements in decision making via spin-valves, spin-transistors, nonvolatile storage devices, and even quantum computing are part of the motivation to pursue full comprehension of spin-polarized materials. In this sense, half-metallic ferromagnetic oxides have attracted extensive attention not only as a source of fully spin-polarized charge carrier for spintronic applications but also as potential candidates for magnetoelectronic elements by virtue of their colossal magnetoresistance. , In 1998, Kobayashi et al reported a large low-field magnetoresistance effect in the double perovskite Sr 2 FeMoO 6 (SFMO) with a fairly high magnetic transition temperature T C of about 415 K which provided intriguing opportunities to explore magnetoelectronic materials showing half-metallic characteristics at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Should the development of fully spin-polarized materials succeed, the field of spintronics would boost the electronic industry with much smaller and robust devices with intrinsic memory. Improvements in decision making via spin-valves, spin-transistors, nonvolatile storage devices, and even quantum computing are part of the motivation to pursue full comprehension of spin-polarized materials. In this sense, half-metallic ferromagnetic oxides have attracted extensive attention not only as a source of fully spin-polarized charge carrier for spintronic applications but also as potential candidates for magnetoelectronic elements by virtue of their colossal magnetoresistance. , In 1998, Kobayashi et al reported a large low-field magnetoresistance effect in the double perovskite Sr 2 FeMoO 6 (SFMO) with a fairly high magnetic transition temperature T C of about 415 K which provided intriguing opportunities to explore magnetoelectronic materials showing half-metallic characteristics at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Heusler ferromagnets (FM) have cubic crystal structures that can often be combined with III-V and IV semiconductors (SC), making it possible to create latticematched heterojunctions by molecular beam epitaxy (MBE). Heusler alloys have hence been used as spin injection layers to create a variety of devices including spin-transistors 6,7 and spin-valves. [8][9][10] Vertical spin-selective devices made of FM/ SC/FM thin film stacks were envisaged recently.…”
mentioning
confidence: 99%
“…4 Therefore, it is hoped that the use of an HA in contact with an AFM as the pinned reference layer would lead to SV or MTJ with ultrahigh magnetoresistive effect amplitudes. Reports on EB in bilayers containing HA are still rare and are restricted to a few reports on HA/AFM bilayers in MTJs including Co 2 MnSi/IrMn, 10,11 Co 2 FeAl/IrMn, 12 or Co 2 FeSi/IrMn [13][14][15] bilayers. In particular, it was shown that Co 2 MnSi/Al-O/Co 2 MnSi/IrMn MTJ can exhibit a large tunnel magnetoresistance of 570% at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…10 Ohdaira et al reported a spin transistor structure consisting of two MTJ with Co 2 MnSi with excellent characteristics. 11 Endo et al reported grain size distribution influence of both AFM IrMn and Co 2 FeSi layers on the magnetic properties of exchange-biased films with H EB of 100-200 Oe. 14,15 They showed that sharp interfaces matching is required between 8 and 10 nm IrMn grains and 15 nm Co 2 FeSi grains to exhibit a large H EB .…”
Section: Introductionmentioning
confidence: 99%